Looks Like Viscera: Folds, Wraps, and Relations in the Southern Andes. Issue 2 (1st June 2019) - Pazzarelli, Francisco
Abstract : This article explores how viscera, bodies, and forces emerge in resemblance to one another. In the connections between the animals' butcher, the treatment of body parts, and the rituals of herd marking in the Argentinean highlands, folds and wrappings of viscera, leathers, meats, and dances make things 'look like' something else in different scales, highlighting correspondences or reflections between entities. Each level of these compositions refers to another, and a change in one can affect all of them. Resemblances are constantly evaluated and topologically manipulated, either to enable their mutual stimulation or to avoid connections and thus to establish differences between the perspectives of different beings. This article argues that the fabrication of similarities and differences through the manipulation of resemblances offers a privileged key to an understanding of Andean and Amerindian sociality.